Understanding the usage of physical activity tracking devices - Lam, Pui Shan (Nanyang Technological University, 2020)
Physical activity tracking devices are currently marketed and popularised as tools that would increase physical activity levels. However, many users stop using them after less than a year. This study aimed to explore reasons for using a physical activity tracker, discontinuation of usage of the device and for non-usage of the device. A total of 305 participants completed a self-reported questionnaire of which 160 participants were currently using an activity tracker, 58 were past users and 87 had never used one before. Older participants tended to use an activity tracker if it was given for free compared with younger participants (p = 0.010). Participants who used a tracker for more than a year before eventually stopping usage had a significantly higher score for device breakage (p = 0.030) or having experienced negative psychological impacts (p = 0.001) as compared to those who used a tracker for less than a year before stopping usage. There is a significant difference for the reasons people did not think that it would help them increase their physical activity level or they did not want to increase their physical activity level with p = 0.001 and p = 0.006 respectively when comparing between those interested and uninterested in using an activity tracker in the future. In conclusion, the most cited reasons for usage were that the tracker was free and the most cited reasons for non-usage of activity trackers were not wanting to increase physical activity levels.